Westonci.ca is your go-to source for answers, with a community ready to provide accurate and timely information. Experience the ease of finding reliable answers to your questions from a vast community of knowledgeable experts. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
Answer:
Step-by-step explanation:
Let's solve your system by substitution.
2x+3y=15;x+y=6
Rewrite equations:
x+y=6;2x+3y=15
Step: Solvex+y=6for x:
x+y=6
x+y+−y=6+−y(Add -y to both sides)
x=−y+6
Step: Substitute−y+6forxin2x+3y=15:
2x+3y=15
2(−y+6)+3y=15
y+12=15(Simplify both sides of the equation)
y+12+−12=15+−12(Add -12 to both sides)
y=3
Step: Substitute3foryinx=−y+6:
x=−y+6
x=−3+6
x=3(Simplify both sides of the equation)
Answer:
x=3 and y=3
Answer:
x = 3, y = 3
Step-by-step explanation:
Given the 2 equations
2x + 3y = 15 → (1)
x + y = 6 → (2)
Multiplying 2) by - 2 and adding to (1) will eliminate x
- 2x - 2y = - 6 → (3)
Add (1) and (3) term by term to eliminate x
y = 3
Substitute y = 3 into either of the 2 equations and solve for x
Substituting into (1)
2x + 3(3) = 15
2x + 9 = 15 ( subtract 9 from both sides )
2x = 6 ( divide both sides by 2 )
x = 3
Visit us again for up-to-date and reliable answers. We're always ready to assist you with your informational needs. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.